The effect of metal‐rich growth conditions on the microstructure of ScxGa1−xN films grown using molecular beam epitaxy. Issue 12 (24th August 2015) - Tsui, H. C. L.; Goff, L. E.; Barradas, N. P.; Alves, E.; Pereira, S.; Beere, H. E.; Farrer, I.; Nicoll, C. A.; Ritchie, D. A.; Moram, M. A.
Abstract : Epitaxial Sc x Ga1− x N films with 0 ≤  x  ≤ 0.50 were grown using molecular beam epitaxy under metal‐rich conditions. The Sc x Ga1− x N growth rate increased with increasing Sc flux despite the use of metal‐rich growth conditions, which is attributed to the catalytic decomposition of N2 induced by the presence of Sc. Microstructural analysis showed that phase‐pure wurtzite Sc x Ga1− x N was achieved up to x  = 0.26, which is significantly higher than that previously reported for nitrogen‐rich conditions, indicating that the use of metal‐rich conditions can help to stabilise wurtzite phase Sc x Ga1− x N.